New Aspects of Genetic Basis, Classification and Treatment of Osteogenesis Imperfecta: Literature Review - G. T. Yakhyayeva; L. S. Namazova-Baranova; T. V. Margieva (Union of pediatricians of Russia, 2015)
Osteogenesis imperfecta is characterized by increased congenital brittleness of bones with a broad spectrum of clinical manifestations - from perinatal/lethal form and severe bone deformities to the mildest forms. In most cases, the disease is caused by autosomaldominant mutation in the collagen 1 gene. At present, the approach to patients with osteogenesis imperfecta is multidisciplinary. Bisphosphonate drug therapy is conducted to reduce the incidence of fractures in the process of treatment, which also involves active rehabilitation and surgical correction of bone deformities. A more profound understanding of pathogenesis of osteogenesis imperfecta may lead to a development of new and effective therapeutic approaches capable of improving functional outcomes in patients.